Characterization of the temperature-humidity index and heat stress in dairy cattle in two dairy units in Mayabeque province, Cuba. - Enríquez, Ana V.; Álvarez Adán, A. (Cuban Journal of Agricultural Science, 2020)
The influence of environmental factors in dairy cows was evaluated. A database that included twelve years (2005-2016) was used. The variables ambient temperature, relative humidity, rainfalls and temperature - humidity index in heat stress levels were studied. The INFOSTAT program was used for the analysis. The results show a high level of the average annual maximum temperature (30.2 ºC). The same performance showed the relative humidity (76.0 %), while rainfalls did not behave in the same way, and tended to decrease by 150 mm during the analyzed period. The average temperature - humidity index was 78 in the period 2005-2016, with marked contrast in its annual distribution. Between November and March, the animals were in slight stress, as opposed to the June- September period, in which the values reached levels of 83, so the animals were exposed to severe stress conditions. During the study period, the average annual relative humidity in the research area was 76 %. Seven months maintained their average monthly value above this value (78 %). In general, an area with high relative humidity can be considered, which has its direct effect on thermal sensation and the temperature-humidity index, which considerably affects the animal welfare. It was proved that during the studied period (2005-2016) the cows were with a level from slight to severe heat stress in all months of the year, which could affect homeostasis and animal welfare. Key words: stress, temperature, humidity, precipitations.